Optimal conditions of mycelial growth of three wild edible mushrooms from northern Thailand - Karunarathna, Samantha C.; Hyde, Kevin D.; Chukeatirote, Ekachai; Klomklung, Namphung (Acta Biologica Szegediensis, 2014)
In this study, three wild mushrooms namely Lentinus connatus, L. roseus, and Pleurotusgiganteus were selected to study if they could be domesticated. Initially, the fruiting bodies of the three mushrooms were collected from forests in northern Thailand and morphologically characterized. In this paper we report the optimal in vitro culture conditions of three wild mushrooms. Among seven culture media tested for the optimal mycelial growth of three wild mushrooms, black bean agar, red bean and soy bean agar were the best for the mycelial growth of L. connatus, L. roseus and Pleurotusgiganteus, respectively. The mushroom mycelia were able to grow at temperatures ranging from 20-30 °C, with optimal growth temperatures of 30 °C and 25 °C for Lentinus and Pleurotus species, respectively. The optimum pH range observed for mycelial growth was 5.0 - 7.0.